Minor hallucinations in Parkinson’s disease with probable rapid eye movement sleep behavior disorder - Jiang, Yinyin; Zhu, Jun; Zhao, Yang; Li, Dongfeng; Chen, Yaning; Wang, Yaxi; Jiang, Xu; Shen, Bo; Pan, Yang; Yan, Jun; Han, Feng; Zhang, Li (Frontiers in Neuroscience, 2023)
Background: Rapid eye movement sleep behavior disorder (RBD) and minor hallucinations (MHs) are prevalent nonmotor symptoms in Parkinson's disease (PD). The purpose of this study was to explore the association of MHs in PD patients with probable RBD (pRBD).This cross-sectional study included 291 patients diagnosed with PD. Patients who scored 6 or higher on the Rapid Eye Movement Behavior Disorder (RBD) Screening Questionnaire were defined as pRBD. A comprehensive evaluation was performed for all patients, including the collection of demographic information, clinical assessment, and MH features.Results: Among the 291 PD patients, 69 (23.7%) had pRBD. MHs were observed in 35 (50.7%) patients with pRBD, significantly higher than 29.7% in patients without RBD (P = 0.015). The main type of MHs in pRBD was presence hallucinations with variable content. Patients with pRBD and MHs tended to be older, had a longer disease duration, and were more likely to take levodopa or dopaminereceptor agonists. Besides, the pRBD with MHs group had higher scores on the Nonmotor Symptoms Questionnaire (NMS-Quest) and Hamilton Anxiety Scale (HAMA). Binary logistic regression analysis revealed that longer disease duration and higher NMS-Quest scores were associated with MHs in PD patients with pRBD.A high prevalence of MHs was observed in PD patients with pRBD. The main type of MHs in pRBD was presence hallucinations. MHs in PD with RBD are mainly associated with disease duration and severity of nonmotor symptoms. These findings provide new insights into the interaction between MHs and RBD.